Towards a cancer mission in Horizon Europe: recommendations. Issue 8 (4th August 2020) - Berns, Anton; Ringborg, Ulrik; Celis, Julio E.; Heitor, Manuel; Aaronson, Neil K.; Abou‐Zeid, Nancy; Adami, Hans‐Olov; Apostolidis, Kathi; Baumann, Michael; Bardelli, Alberto; Bernards, René; Brandberg, Yvonne; et al.
Abstract : A comprehensive translational cancer research approach focused on personalized and precision medicine, and covering the entire cancer research–care–prevention continuum has the potential to achieve in 2030 a 10‐year cancer‐specific survival for 75% of patients diagnosed in European Union (EU) member states with a well‐developed healthcare system. Concerted actions across this continuum that spans from basic and preclinical research through clinical and prevention research to outcomes research, along with the establishment of interconnected high‐quality infrastructures for translational research, clinical and prevention trials and outcomes research, will ensure that science‐driven and social innovations benefit patients and individuals at risk across the EU. European infrastructures involving comprehensive cancer centres (CCCs) and CCC‐like entities will provide researchers with access to the required critical mass of patients, biological materials and technological resources and can bridge research with healthcare systems. Here, we prioritize research areas to ensure a balanced research portfolio and provide recommendations for achieving key targets. Meeting these targets will require harmonization of EU and national priorities and policies, improved research coordination at the national, regional and EU level and increasingly efficient and flexible funding mechanisms. Long‐term support by the EU and commitment of Member States to specialized schemes are also needed for the establishment and sustainability of trans‐border infrastructures and networks. In addition to effectively engaging policymakers, all relevant stakeholders within the entire continuum should consensually inform policy through evidence‐based advice. Abstract : A comprehensive cancer approach covering the entire research–care–prevention continuum can achieve a 10‐year cancer‐specific survival for 75% of patients diagnosed in EU member states with well‐developed health care by 2030. To ensure access to a critical mass of patient biological and technological resources, infrastructures for translational research, clinical and prevention trials, and outcomes research are needed. Here, we provide recommendations for achieving key targets and prioritize research areas.